Integrating Performance Measurement Systems Into the Global Lean and Sustainable Construction Supply Chain Management - Tatlici, Gamze; Sertyesilisik, Begum (IGI Global, 2019)
The construction industry is one of the industries that have a great impact on the economy. A construction supply chain (CSC) is an important process affecting the circular economy (CE) and sustainability in practice. In order to analyze the efficiency of CE and CSC, a performance measurement system (PMS) is needed. At such a point, adopting a PMS to a supply chain at relatively early stages of a project could lead to sustainable supply chain management (SCM). Collaboration between all parties such as designers and contractors will be advantageous to gain competitiveness in the sector. This chapter aims to determine the need of PMS adaptation to construction supply chain process for sustainable and lean construction supply chain management based on the literature review. This chapter is expected to be beneficial for academics, researchers in the relevant field as well as policy makers and professionals.